Home alone 3 : a novelization - Strasser, Todd. (New York : Scholastic, 1997)
Alex hates having to stay home from school because there is nothing to do, but when he sees someone breaking into his neighbor's house and no one believes him, he realizes it is up to him to save his neighborhood.
"Based on the hilarious new film from Twentieth Century Fox"--Cover.
4.8
3-6
3-6
Keywords: Burglary -- Fiction; Self-defense -- Fiction; Theft -- Fiction; Self-defense -- Fiction